Relationships Among Leaders' and Followers' Work Engagement and Followers' Subjective Career Success: A Multilevel Approach - Chen, Qishan; Yang, Shuting; Deng, Jiayu; Lu, Liuying; He, Jingyi (Frontiers in Psychology, 2021)
Using a sample of 52 work teams (52 work team leaders and their 348 followers) in China, we investigated the influence mechanism of leaders' work engagement on their followers' work engagement and subjective career success. A multilevel structural equation model (MSEM) was applied to analyze the survey data. The results of this study indicated that leaders' work engagement positively influenced their followers' subjective career success, and this relationship was mediated by the followers' work engagement. Implications of these findings, limitations, and directions for future research are discussed in the final section of the paper.